Characterization of the ALSEP Process: Investigating Equilibrium and Intermediate Complexes of the Scrub Stage. Issue 6 (19th September 2022) - Picayo, Gabriela A.; Etz, Brian D.; Eddy, Madeleine A.; Vyas, Shubham; Jensen, Mark P.
ABSTRACT: A unique combination of real-time and conventional optical spectroscopy, off-line chemical analyses, and equilibrium solvent extraction measurements were employed to monitor progressive changes in the speciation of the organic-phase complexes of neodymium or americium in the biphasic scrub stage of the Actinide-Lanthanide Separation (ALSEP) solvent extraction process proposed for trivalent actinide/lanthanide separations. Consistent with the findings of other researchers, four unique organic-phase species are identified by three separate methods of multivariate analysis. The organic phase initially contains M(TEHDGA)2 (HEH[EHP])2 (NO3 )3 complexes. As the ALSEP organic phase is scrubbed with an aqueous malonate buffer, the complex loses HNO3 to form M(TEHDGA)2 (H(EH[EHP])2 )(NO3 )2 as the first organic-phase intermediate species. Further contact with the scrub aqueous phase forms a second intermediate species, M(TEHDGA)(H(EH[EHP])2 )2 (NO3 ), and eventually a complex containing only HEH[EHP], MH(EH[EHP])2 3 (where TEHDGA = N, N, N ', N '-tetra(2-ethylhexyl)diglycolamide and HEH[EHP] = 2-ethylhexyl phosphonic acid mono-2-ethylhexyl ester). Similar intermediate species were also observed in equilibrium ALSEP organic phases when lower aqueous concentrations of nitric acid (e.g., 0.5 M HNO3 ) were used to extract actinides or lanthanides.